Association Between Personality Disorders Traits and Problematic Cannabis Use in Adolescents. (16th April 2015) - Chabrol, Henri; Melioli, Tiffany; Goutaudier, Nelly
<x xml:space="preserve">Abstract</x> Background: There are few studies on the contribution of personality disorder traits to cannabis use disorders in adolescents. Objectives: The aim of the study was to evaluate the association of personality disorder traits to problematic cannabis use. Methods: Participants were 111 high school students who completed self-report questionnaires, mainly the Cannabis Use Disorders Identification Test, assessing problematic cannabis use, and the Personality Diagnostic Questionnaire using the scales evaluating personality disorders most often linked to adolescent cannabis use. Results: A multiple regression analysis showed that personality disorder traits explained a high part of the variance in problematic cannabis use symptoms. Schizotypal and borderline personality traits were positively associated to problematic cannabis use symptoms after adjustment for anxious and depressive symptoms. Conclusions: This study suggests the importance of evaluating personality disorder traits in studies of risk factors or consequences of problematic cannabis use.